Islam's Interest in Infrastructure; A Descriptive Historical Study: عناية الإسلام بالبنية التحتية; دراسة تاريخية وصفية - Ubaid Hasan Saleh, Abdulmajid; Assaghir Bahmi, Abdulrahim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
بحث فقهاء الإسلام العقود بشكل عام في الفقه الإسلامي، وتناولوا جُل المباحث العقدية المالية بالدراسة والتحليل الفقهي، بينما قل ما تجد جد دراسة مستوفية لواقع الاهتمام بالبنية التحتية من الناحية التاريخية وإبراز ذلك من الجانب المقاصدي، فخلفاء الإسلام كانوا حريصين على العمران كتعبيد الطرقات، وتوفير الإضاءة، ومشاريع المياه، والمستشفيات، بحسب متطلبات تلك المرحلة وإمكانيتاها، وقد كان الاهتمام ببناء المساجد والمدارس وتوفير المياه مبكراً، فإن أول حدث يطالعنا في هجرة النبي صلى الله عليه وسلم بناء المسجد (الذي كان يعتبر مركز عبادة وقضاء وتعليم)، ثم الحث على شراء بئر رومة، وقد أثنى النبي صلى الله عليه وسلم على من أسرج المسجد وسماه سراجا، وتعتبر دار الأرقم ابن أبي الأرقم مركز تعليمي، وقد كان يسمى (دار القراء) كل هذه الأحداث تبين اهتمام الشريعة بالبنية التحتية، تأصيلاً، وتطبيقاً، وعلى هذا الأمر سار كثيراً من خلفاء العصر الإسلامي، وهذ الأمر يحتاج إلى إبراز لتعزيز الفكر الإسلامي المعاصر وبيان كلية الدين، من حيث اهتمامها بكافة الجوانب الحياتية. الكلمات المفتاحية: البنية التحتية، العمران، العصر الإسلامي. Abstract Jurists discussed the matter of contracts in Islamic jurisprudence generally. They dealt with study and analysis most of the financial ideological issues in jurisprudence. However, there is a scarceness in competent studies that meet the reality of interest in infrastructure from historical terms as well as highlighting this from the lawful side. Moreover, we can see that the successors of Islam were aware for the matter of urbanism such as paving roads, providing lighting, water projects, and hospitals, according to the requirements and possibilities of that stage. Consequently, the interest in building mosques and schools as well as providing water early, appeared clearly; so, the first event which we read it in the migration of the Prophet (PBUH) was the construction of the mosque (which was considered a center of worship, justice and education), and then urged the purchase of a 'Ruma Well'. Furthermore, the Prophet (PBUH) praised that one who lightened the mosque and called him a 'Sraj' (light). In addition, we cannot forget 'Dar Al-Arkam ibn Abi Al-Arkam' which considered an educational center, which was called 'Dar Al-Qra'a' (House of Readers). Therefore, all these events show the interest of Sharia in infrastructure on the provenance and application. As such, many of the successors of the Islamic era have followed, for that; this matter needs to be highlighted to promote contemporary Islamic thought and the statement of the reality of religion, in terms of its interest in all aspects of life. Keywords: Infrastructure, Urbanism, Islamic Era.